THE EMPIRICAL STUDY ON THE DETERMINANTS OF MOSLEM CONSUMERS TO PURCHASE HALAL PRODUCTS - Mahiah bt. Hj Said; Khairul Nizam bin Surbaini; Mohd Anuar bin Awang Idris (Journal of Management and Business, 2010)
Nowadays, the issue of Halal has been debated and argued by so many parties and Moslem consumers in Malaysia have to select acceptable food products which contain many ingredients in varying quantities, including trace amounts of haram or questionable ingredients. Halal starts from the very beginning of food preparation process until the product reaches the consumer. Thus, it must be prepared, processed, manufactured and storage using equipment untainted by anything unclean (S. Shafie and O. Mohamad, 2002). The primary objective of this study is to identify the determinants of Halal perceived by the Moslem consumer in Malaysia and measuring the consumer perception on the Malaysia Halal certification. This study presents primary data collected by self-administered statements involving 385 responses from the Moslem respondents within concentration in Klang Valley and East Coast region of Malaysia. The factors are analyzed using factor analysis with varimax rotation, to cluster the criteria into several variables to determine the dimensions of Moslem consumers’ perception towards Halal food produce. The result shows that religiosity commitment is a significant determinant for Moslem consumer to purchase Halal products in Malaysia. We also found encouraging result that shopping orientation is among important factor by Muslim consumers in their buying behavior towards Halal products.